Investigation of the deformation behavior of pure titanium with different self-consistent models. (June 2022) - Zhang, Pengfei; Chapuis, Adrien; Xin, Yunchang; Liu, Qing
Abstract: The mechanical properties of an annealed commercially pure Ti plate were investigated. Tension and compression tests were made at room temperature, and EBSD was used to characterize the initial and deformed microstructures. The visco-plastic self-consistent model with an empirical Voce hardening law was used to reproduce the material behavior. Several self consistent schemes (SCS) were used, and the simulated twin volume fractions, textures and plastic anisotropy ( r -values) were compared with experimental data. The hardening of slip modes by twinning were taken into account by latent hardening coefficients. Only the Tangent SCS allows reproducing perfectly all the stress-strain curves, but the latent hardening for prismatic slip by tension twinning must be higher in compression than in tension. It is found that under compression, tension twinning and prismatic slip compete and impede each other, so tension twinning dramatically increases the critical resolved shear stress (CRSS) of all slip modes, which is modeled by a strong latent hardening. But under tension, tension twins grow in undeformed matrix and slightly increase the CRSS for prismatic slip, resulting in a low latent hardening. The Tangent SCS can also reproduce better the r-values. The deformed textures predicted by all the SCS except Secant are similar. Simulations show that the CRSS for pyramidal slip is higher than the CRSS for basal slip. Graphical Abstract: ga1